Instilling National Values Through Local Culture-Based Character Education - Ibrahim, Fahmi; Sundawa, Dadang (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to identify how culture-based character education internalizes national values. Character education must be introduced to the younger generation as they leave the local culture. This study used a qualitative approach with a literature review method. It used secondary data from relevant books, articles, and other literature. Data were analyzed using the Critical Discourse Analysis (CDA) model. This study showed that character education based on local culture could instill national values. National values covered religion, mutual cooperation, local art and literature, and local skills values. It is essential to provide character education to the young generation to instill national values that begin to fade. This country is rich in local cultures, and they must be introduced to a young age as globalization can fade local culture.